Épistémologies du Sud : lectures critiques du féminisme décolonial - Femenías, María Luisa (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2019)
Publié en 2000, le livre de Boaventura de Sousa Santos — un sociologue émérite portugais — intitulé Critique de la raison indolente a eu un grand impact au Brésil comme dans le reste de l’Amérique Latine (De Sousa Santos, 2000/2003). Il y développait ce qu’il a appelé « les Épistémologies du Sud » global en opposition aux « Épistémologies du Nord », global également. De Sousa Santos entendait par « Épistémologies du Sud » les connaissances, théories et savoirs qui réfléchissent avec créativit...
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 5-Autrice; _Nettoyé

Equivocation, Translation, and Performative Interseccionality: Notes on Decolonial Feminist Practices and Ethics in Latin America - de Lima Costa, Claudia (ANGLO SAXONICA, 2013)
In this paper I offer a brief overview of the academic debates about post-colonial theories and the concept of coloniality, seeking to map out their Latin American translations, especially from the perspective of feminist theories in relation to the coloniality of gender. By emphasizing an intersectional approach to understand the gendered character of coloniality, decolonial feminists are seeking innovative ways of articulating new epistemologies or “saberes propios”. However, in these debates little attention has been given to the issue of the travels and translations of decolonial feminisms in Latin America. In focusing on the vexed issue of translation, I want to explore some of the challenges Latin American decolonial feminists are facing today.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Representaciones del espacio, el tiempo y las mujeres indígenas en fotografías, siglos XIX-XXI - Yujnovsky, Ines (Memoria y Sociedad, 2017)
Este trabajo se propone comprender la incidencia de las relaciones de poder que ciertas representaciones temporales acerca de grupos indígenas pueden ejercer en nuestra comprensión pasada y actual. Diversas imágenes reprodujeron ideas de indígenas que, aunque estuvieran vivos, mostraban una cultura asimilada a un pasado de amplias dimensiones. Por lo tanto, para comprender el proceso de invisibilización de la diversidad indígena en la cultura nacional, es relevante considerar los mecanismos de montaje discursivo —visuales y textuales—, vinculados con las nociones temporales de indios viviendo en un supuesto tiempo remoto. Atendiendo a ello, se analizan los procesos de montaje, desde la producción de las fotografías hasta la edición y presentación de imágenes, tanto en la prensa como en postales, publicaciones científicas y de divulgación, para ver cómo a veces pequeños cambios de encuadre, contraste, retoque o selección pueden incidir en la construcción de diversas historias, en la comprensión y en los sentidos construidos y en pugna.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Arte contemporáneo, violencia y creación feminista. "Lo personal es político" y la transformación del arte contemporáneo - Collado, Ana Martínez (Dossiers feministes, 2014)
Este texto analiza la transcendencia de la revolución feminista que se inició en los años 60 a partir del lema «Lo personal es político» y su influencia en la transformación del arte contemporáneo. En este contexto el trabajo desarrollado por las prácticas artísticas y la crítica feminista en relación a la denuncia de la violencia contra la mujer ocupa una posición destacada. A lo largo de estas últimas décadas no sólo ha evidenciado la violencia como un hecho continuado y global hacia la mujer sino que, además, ha iniciado nuevas narraciones que dan respuesta a un drama considerado socialmente como un irremediable «trágico final».
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Feminist Geographies in Latin America: Epistemological Challenges and the Decoloniality of Knowledge - Silva, Joseli Maria; Ornat, Marcio Jose (Journal of Latin American Geography, 2020)
This paper analyzes the growth of gender studies in Latin America, despite facing resistance in the scientific field and from the advance of conservative policies on the continent. It also addresses the challenges that feminist research faces in colonized spaces. To develop our argument, we draw on the scholarship of feminist researchers in Brazil, Mexico, and Argentina, such as Veleda da Silva and Lan (2007), Silva and Vieira (2014), Silva, César and Pinto (2015), Colombara (2016), Lan (2016), Veleda da Silva (2016), Ibarra-García and Escamilla-Herrera (2016), Zaragocin-Carvajal, Moreano-Venegas, and Álvarez-Velasco (2018), and Silva and Ornat (2019). This paper also examines the difficulties that Latin American feminist geographies face in establishing their own foundations in a globalized world where the geopolitics of global knowledge of geography is increasingly structured by the epistemological centralization of the Anglophone northern hemisphere.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Corporeal Identities, Maternal Artivism: A New Decolonial Approach to the Study of Latin American Women Artists - Demori, Lara (Arts, 2019)
Stemming from Grosfoguel’s decolonial discourse, and particularly his enquiry on how to steer away from the alternative between Eurocentric universalism and third world fundamentalism in the production of knowledge, this article aims to respond to this query in relation to the field of the art produced by Latin American women artists in the past four decades. It does so by investigating the decolonial approach advanced by third world feminism (particularly scholar Chandra Talpade Mohanty) and by rescuing it from—what I reckon to be—a methodological impasse. It proposes to resolve such an issue by reclaiming transnational feminism as a way out from what I see as a fundamentalist and essentialist tactic. Following from a theoretically and methodological introduction, this essay analyzes the practice of Cuban-born artist Marta María Pérez Bravo, specifically looking at the photographic series Para Concebir (1985–1986); it proposes a decolonial reading of her work, which merges third world feminism’s nation-based approach with a transnational outlook, hence giving justice to the migration of goods, ideas, and people that Ella Shohat sees as deeply characterizing the contemporary cultural background. Finally, this article claims that Pérez Bravo’s oeuvre offers the visual articulation of a decolonial strategy, concurrently combining global with local concerns.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé